BACTERIAL COMMUNITY SHIFTS OF A HIGH MOUNTAIN LAKE IN RESPONSE TO VARIABLE SIMULATED CONDITIONS: AVAILABILITY OF NUTRIENTS, LIGHT AND OXYGEN - MUNTI YUHANA; THOMAS HORATH; KURT HANSELMANN (SEAMEO BIOTROP, 2006)
We studied bacterial population composition shifts by exposing natural water samples to variable simulated environmental conditions. The samples were taken from Lake Jori XIII (2640 m a.s.l), an oligo-to mesotrophic cold freshwater lake, located in the eastern Swiss Alps. The Jori lakes are characterized as remote, unpolluted high mountain lakes with a long period of ice cover and typically low nutrient concentrations. Culture independent techniques (PCR-based analyses) were used for detection and molecular characterization of a large number of bacteria most of which are still uncultivable. Bacterial community shifts over three ecological conditions (nutrients, light and oxygen availability) were detected by using Temporal Temperature gradient Gel Electrophoresis (TTGE) of a PCR-amplified part of the 16S rRNA gene. The bacterial populations responded differently to the variable conditions, as revealed by TTGE pattern shifts during the experiment. Key words: Temporal Temperature gradient Gel Electrophoresis (TTGE), ARB, small subunit ribosomal RNA gene (SSU rRNA gene), alpine freshwater lake JOri XIII, PCR